Pewarisan Nilai-Nilai Tradisi Lisan Nyale dan Pasola dalam Masyarakat Sumba Bagian Barat: Kajian Sosiologi Sastra - Banda, Maria Matildis; Mas Triadnyani, I Gusti Agung Ayu (Humanis; Vol 28 No 4 (2024)DO - 10.24843/JH.2024.v28.i04.p06, 2024)
Nyale is a tradition of catching (picking up) sea worms. Pasola is a horse-drawn war between two groups of participants, throwing javelins to knock down their opponents. Nyale and pasola have been passed down from generation to generation in the western part of Sumba, especially in Southwest Sumba and West Sumba Regencies.  This tradition takes place in February and March every year. This unique tradition needs to be publicized through various platforms, so that the inheritance of values can be more widely known. One of them is changing the vehicle into literary works.  This article will explain the nature of nyale and pasola; Nyale and Pasola myths; and the inheritance of the Nyale and Pasola oral traditions through literary works. This question was answered through participatory qualitative field research and literature study. The theory used is the sociological theory of literature with the support of oral tradition theory, myth theory, and change form (vehicle transfer theory) theory. The results explain that nyale and pasola are traditions that underline the importance of honesty and expressing gratitude for the harvest. The meaning of nyale and pasola is living together to support traditions, the role of horses in pasola, the role of traditional elders, as well as various traditional wisdom as teachings of life. This idea about the meaning of nyale and pasola was then transferred into a literary work, the novel Pasola.